Public transport in a small island of a developing country - Rahman, M. Shafiq-Ur (Revista Brasileira de Gestão Urbana, 2017)
This paper explores the existing forms of public transport system and their services as well as travel patternof people in Siquijor Province, an island of the Philippines. Household questionnaire survey, interview ofthe passengers of various public transport modes at their stations, and a detailed participatory observationwere conducted for the research. Bus, jeepney3, easyride4, tricycle5, and habalhabal6 are the available publictransport systems in the island. However, these services do not provide travel time, waiting time, availabilityor frequency, comfort, and safety that is required by passengers. Majority of the people mostly prefer theeasyride for comfort and less waiting time whilst the bus for comfort. Considering the travel pattern, socioeconomicsituation and topographic condition, the research tried to identify which form of public transportsystem would be appropriate for the island. It was found that bus is appropriate for longer trips while easyridefor the inter-municipal trips and habalhabal for the trips in mountain areas.